Factors Associated with Willingness for Sputum Examination Among Tuberculosis Suspects and Risk Groups at Ambarita Health Center, Samosir Regency - Br. Tobing, Netty Elida; Khadijah, Siti; Ashar, Taufik (RIRAI Publisher, 2024)
Tuberculosis (TB) is an infectious disease that remains an important global and Indonesian public health problem. Optimizing case finding is one of the strategies to control TB in Indonesia, but TB case finding only reached 74.7 percent out of a target of 90 percent in 2022. The delay in case finding is due to the lack of public awareness to check themselves to health care facilities and many people refuse to have their sputum examined. This study aims to determine the factors associated with the willingness to conduct sputum examination in suspected TB and at-risk groups at the Ambarita Health Center, Samosir Regency. This type of research is quantitative with a cross sectional design. The study population was TB suspects and people who have household contact with TB patients. A sample of 118 people was selected using simple random sampling. The results showed that age (p=0,021; PR=2,433; 95% CI= 1,198–4,943), knowledge (p=0,016; PR=2,523; 95% CI= 1,243–5,120), and perception (p=0,009; PR=3,061; 95% CI= 1,316–7,118) were associated with the willingness to conduct sputum examination among TB suspects and at-risk groups at the Ambarita Health Center, Samosir Regency, while gender (p=1,000), education (p=0,110), occupation (p=0,211), and income (p=0,145) were not. The health center is expected to provide education and counselling to the community and form a group of TB survivors to help provide social support and share experiences about the course of TB disease to increase knowledge and build good perceptions of TB disease.